2018
DOI: 10.2174/0929867325666180214110932
|View full text |Cite
|
Sign up to set email alerts
|

Natural Terpenoids Against Female Breast Cancer: A 5-year Recent Research

Abstract: These compounds appear to be promising to overcome breast cancer treatment failure. However, despite the interesting activities, additional preclinical investigations are needed in further breast cancer cell/tumor models in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…Celastrol, derived from the Chinese herbal medicine Trypterygium, exhibits extensive biological and pharmacological activities. Zhang J claimed that celastrol ameliortes inflammation on Human Retinal Pigment Epithelial Cells .…”
Section: Introductionmentioning
confidence: 99%
“…Celastrol, derived from the Chinese herbal medicine Trypterygium, exhibits extensive biological and pharmacological activities. Zhang J claimed that celastrol ameliortes inflammation on Human Retinal Pigment Epithelial Cells .…”
Section: Introductionmentioning
confidence: 99%
“…In 1970 s, triptolide was first isolated from traditional Chinese herb Tripterygium wilfordii HOOK F. and purified. 25) As the progress in pharmacological research of triptolide, it has been reported to exhibit a clinical significance in anti-cancer treatment. 26,27) Previous studies have showed that more than one signaling pathway attributing to the anti-tumor effect of triptolide.…”
Section: Discussionmentioning
confidence: 99%
“…The metastasis involves dissemination of cancer cells and is the leading cause of mortality in breast cancer patients [ 3 ]. With advances in understanding the pathogenesis of breast cancer, many natural phytochemicals have been reported to be promising for treatment of female breast cancer [ 4 ]. However, more studies are needed to better understand their pharmacology in treating TNBC.…”
Section: Introductionmentioning
confidence: 99%